Allaiter de sang le poème. la légende roumaine de Maître Manole chez Benjamin Fondane et Paul Celan - Gisèle Vanhese (Revista de Istorie și Teorie Literară)
This study is following the motif of creation myth based on a human sacrifice. The myth of the woman walled in is very popular to several Eastern cultures from Balkans, as well as Serbians, Romanians, Greeks, Albanians. The authoress analyse this motif between two Romanian writers: Benjamin Fondane and Paul Celan, because it is there that the myth of sacrifice appear as a metaphor of lyrical creation.